Network classification for traffic management : anomaly detection, feature selection, clustering and classification - Tari, Zahir, 1961-; Fahad, Adil; Almalawi, Abdulmohsen; Yi, Xun (College teacher) (Institution of Engineering and Technology, 2020)
The book investigates network traffic classification solutions by proposing transport-layer methods to achieve better run and operated enterprise-scale networks. It deals with the following subjects: traffic management; anomaly detection; clustering algorithms; unsupervised feature selection; transport layer statistics quality; feature set; privacy preserving framework for traffic data publishing; semi-supervised approach for network traffic labelling; and hybrid clustering-classification.
Keywords: Telecommunication -- Traffic -- Management.; Computer network protocols -- Management.; elektronické knihy; electronic books